Land in Motion. Issue 4 (3rd July 2016) - Bergmann, Luke; Holmberg, Mollie
Abstract : Globalization entwines human lives with distant fields and forests. In response, our approach to land is relational yet also computational. We calculate and map intricate connections among land uses and distant populations mediated by both commodity chains and capital, thereby unpacking, deepening, extending, and pluralizing recent methods estimating land footprints of commodity consumption. After constructing networks of approximately 130 million direct connections among land uses, economic activities, and peoples of the world in 2007, we trace infinities of indirect interconnections. Dominant absolute-space approaches to human–environment relations facilitate local comparisons of population and resources, but our relational quantitative approach provides maps and metrics that illustrate how uneven development under neoliberal globalization results in strong global net redistributions of various per capita benefits from land use, especially from Global South to Global North. From the perspective of capital investment, the median square meter of global land use contributes to futures of human populations outside, not inside, of the country of that land. Many connections to land reach us in the form of manufactured goods and services, not just through food and fibers. Our conclusions require simultaneous examination of the indirect interconnections of all commodities, activities, and places; our characterizations of land and globalization thus differ from the forms of evidence used in studies examining single commodity chains or offered by direct trade statistics, although the results are often complementary. We show that geographical political economy and relational quantitative approaches to space have much to offer understandings of land in the Anthropocene.